Helicobacter pullorum: An Emerging Zoonotic Pathogen - Javed, Sundus; Gul, Farzana; Javed, Kashaf; Bokhari, Habib (Frontiers in Microbiology, 2017)
Helicobacter pullorum (H. pullorum) commonly colonizes the gastrointestinal tract of poultry causing gastroenteritis. The bacterium may be transmitted to humans through contaminated meat where it has been associated with colitis and hepatitis. Despite the high prevalence of H. pullorum observed in poultry, little is known about the mechanisms by which this bacterium establishes infection in host and its virulence determinants. In this article we aim to provide an overview of this emerging zoonotic pathogen; its general characteristics, hosts, prevalence and transmission as well as its pathogenic potential. We also discuss possible control strategies and risk of disease emergence.